Analysis Of Islamic Law Regarding The Crime Of Drinking Alcohol (Syubul Khamr) - Misdin Arifin HM; Naufal Fadhilah (AT-TAFAHUM: Journal of Law, 2021)
This study aims to analyze the crime of drinking alcohol (syurbul khamr) from an Islamic legal perspective, emphasizing the normative basis, forms of prohibition, and sanctions stipulated in the Shari'a. Alcohol, as an intoxicating beverage, is expressly prohibited in the Qur'an and Hadith because it can damage the mind, which is one of the main objectives of safeguarding the maqashid sharia. This study uses a qualitative method with a juridical-normative approach through a literature study of classical and contemporary Islamic legal sources. The results show that the prohibition of alcohol is not only moral, but also has a strong legal dimension with the existence of hudud sanctions for perpetrators. In addition, Islam also applies a preventive approach by prohibiting all activities related to alcohol, including production, distribution, and consumption. In the contemporary context, law enforcement against this crime faces various challenges, but the values contained remain relevant in maintaining social order and community morals. Thus, the prohibition of alcohol in Islam aims to protect individuals and society from physical, mental, and social damage.